Error-Manipulation Gait Training for Veterans With Nontraumatic Lower Limb Amputation: A Randomized Controlled Trial Protocol. Issue 11 (9th August 2021) - Kline, Paul W; So, Noel; Fields, Thomas; Juarez-Colunga, Elizabeth; Christiansen, Cory L
Abstract: Objective: he purpose of this study will be to determine the efficacy of error-manipulation gait training (error-augmentation or error-correction) to improve step length symmetry and secondary health outcomes in veterans with unilateral nontraumatic transtibial amputation (TTA). Methods: This will be a 3-arm, parallel, assessor-blinded, randomized controlled trial, with baseline, postintervention, and 3-month follow-up assessments in a VA Geriatric Research Education and Clinical Center. Participants are 54 US military veterans ranging in age from 50 to 85 years with a unilateral transtibial nontraumatic amputation. Participants will be randomized into 1 of 3 groups: error-augmentation training (EAT), error-correction training (ECT), or supervised walking (CTL). Each group will complete 8 split-belt treadmill walking training sessions of 25 minutes each over 4 weeks. The EAT group will walk with belts moving at asymmetrical speeds. The ECT group will walk to the cadence of a metronome and the split belts moving at symmetrical speeds. The CTL group will walk with symmetrical belt speeds and without feedback. Step length symmetry is the primary outcome and will be assessed using an asymmetry index during overground walking. Secondary outcomes include lower extremity joint work during treadmill walking, 6-Minute Walk Test performance, daily step count, participant-perceived disability, and residual-limb integumentary health. Outcomes will be assessed at preintervention, 1-week postintervention (primary endpoint), and 13 weeks postintervention. Impact: This study protocol focuses on an understudied area of rehabilitation for patients with nontraumatic unilateral TTA who have high levels of spatiotemporal gait asymmetry and mobility impairment. The results of this study will inform future implementation of clinical gait training interventions to improve spatiotemporal gait symmetry and long-term health and disability outcomes in patients with nontraumatic unilateral TTA.